Association of DNA methylation with energy and fear-related behaviors in canines - Sanders, Abigail R.; Bhongir, Neha; vonHoldt, Bridgett; Pellegrini, Matteo (Frontiers in Psychology, 2022)
Behavioral traits are influenced by gene by environment interactions. To study the genetic and epigenetic components of behavior, we analyzed whether dog behavioral traits could be predicted by their DNA methylation and genotypes. We conducted an analysis on dog behaviors such as sociability, trainability and energy as measured by C-BARQ behavioral surveys paired with buccal swabs from 46 dogs. Previously we used targeted bisulfite sequencing to analyze DNA methylation and collected genotype data from over 1500 single nucleotide polymorphisms. Owner-reported C-BARQ responses were used to quantify 14 behavioral trait values. Using Partial Least Squares Regression analysis we found behavioral traits such as energy, attachment/attention-seeking, nonsocial fear, and stranger-directed fear to be significantly associated with DNA methylation across 3059 loci. After we adjusted for age as a confounding variable, energy and stranger-directed fear remained significantly associated with methylation. We found that most behavioral traits were not predictable by our limited set of single nucleotide polymorphisms (SNPs). By identifying individual genes whose methylation is significantly associated with behavioral traits, we generate hypotheses about possible mechanisms involved in behavioral regulation. Overall, our study extends previous work in behavioral epigenetics, shows that canine behaviors are predictable by DNA methylation, and serves as a proof of concept for future studies in behavioral epigenetics.